2016
DOI: 10.1586/14737140.2016.1121106
|View full text |Cite
|
Sign up to set email alerts
|

New investigations into the stability of Mesna using LC-MS/MS and NMR

Abstract: 3 It is important for sarcoma patients to receive the correct dose of Mesna as an adjuvant with Ifosfamide to reduce the risk of haemorrhagic cystitis. This paper describes a study conducted to evaluate the physicochemical stability of Mesna for injection formulation over 14 days.Mesna samples (n=4, 20mg/mL) were incubated in glass vials at 37+0.5ºC. Mesna concentrations were determined by LC-MS/MS, and NMR was used to detect degradation products. Evaporative losses and pH were also monitored.Our results diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…On the other hand, mesna is transformed into dimesna, which is rapidly excreted in urine to create a nontoxic, inert dimer (thioether) on the mucosal surface of UB by direct coupling of dimesna with acrolein [48]. Lack of mesna antioxidant and anti-inflammatory activity limits its effectiveness, leading to ineffective prevention of HC in 25% of cases treated with CP.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mesna is transformed into dimesna, which is rapidly excreted in urine to create a nontoxic, inert dimer (thioether) on the mucosal surface of UB by direct coupling of dimesna with acrolein [48]. Lack of mesna antioxidant and anti-inflammatory activity limits its effectiveness, leading to ineffective prevention of HC in 25% of cases treated with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of (a) His-Au NCs and (b) MES-Au NCs (a) Au nanoclusters were synthesized by blending histidine and chloroauric acid as reported previously. 25,26 Briey, chloroauric acid (5 mL, 0.01 M) was added to the solution of histidine (15 mL, 0.1 M), then stored at 25 C for 2 h without light. The concentration of the as-synthesized His-Au NCs was 2500 mM.…”
Section: Apparatusmentioning
confidence: 99%
“…23 Most of the currently available detection methods were based on instrumental analysis. [24][25][26][27] For example, Mare et al 24 achieved MES detection by using chromatography combined with uorescence detection; Rizk et al 25 adopted high performance liquid chromatography (HPLC) method for simultaneous separation and quantication of MES in the presence of its degradation products; Salman et al 26 showed a reliable and specic LC-MS/MS method for detection of MES and Dimesna; Ling et al 27 performed capillary liquid chromatography to detect MES. Even though the sensitivity of these instrumental analytical methods is relatively high, they are usually complicated in sample pretreatment and high in operation and instrument cost.…”
Section: Introductionmentioning
confidence: 99%